Constitution Of India And Reservation In Promotions - Tyagi, Prerna (Trinity Law Review, 2021)
Fundamental rights are provided with in Part III of the Constitution of India. According to Article 16.4, in the interest of any ’backward class’ of people not sufficiently represented in the state’s public authorities, the State may reserve appointments or offices. Explaining the nature of this article, A.C in Mohan Kumar Singhania v. Union of India stated that it is indeed "an enabling provision" which conferred a discretionary discretion on the State, in favor of any backwards citizens’ class that is not sufficiently represented at the state’s service, to provide, or reserve, appointees or positions. However, in a recent judgment the Supreme Court explained the reservation in promotion as a non-fundamental right. In this paper, I will provide a quick overview of the constitutional history of reservations in public job promotions and its current state of affairs.